2014
DOI: 10.4317/jced.51518
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pulp calcifications and salivary gland calcifications

Abstract: Aim: Pulp stones are discrete calcified bodies found in the dental pulp. Sialolithasis is the most common salivary gland disease. The aim of the present study was to determine the relationship between the pulp stones and salivary gland stones. Material and Methods: 196 patients were randomly selected from the out patient department for the study. The periapical radiographs for all patients were evaluated for the presence or absence of the narrowing of dental pulp chambers and pulp canals. The intra oral occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
3
1
2
Order By: Relevance
“…In a recent study with a large sample, (Berticelli et al, 2018) examined 2444 panoramic radiographs and calculated an incidence of sialoliths of 1.96%. Kaswan et al (2014) studied the prevalence of submandibular sialoliths using periapical and occlusal radiographs and found that 5 of their 196 subjects (2.5%) suffer from submandibular sialoliths, higher than that in our study (1.8%). Similarly, (Vengalath et al, 2014) determined a prevalence of submandibular sialoliths of 4.3% in their sample of 1615 panoramic radiographs, divided equally between males and females.…”
Section: Discussioncontrasting
confidence: 71%
“…In a recent study with a large sample, (Berticelli et al, 2018) examined 2444 panoramic radiographs and calculated an incidence of sialoliths of 1.96%. Kaswan et al (2014) studied the prevalence of submandibular sialoliths using periapical and occlusal radiographs and found that 5 of their 196 subjects (2.5%) suffer from submandibular sialoliths, higher than that in our study (1.8%). Similarly, (Vengalath et al, 2014) determined a prevalence of submandibular sialoliths of 4.3% in their sample of 1615 panoramic radiographs, divided equally between males and females.…”
Section: Discussioncontrasting
confidence: 71%
“…In a recent study with a large sample, Barticelli et al (2018) examined 2444 panoramic radiographs and calculated an incidence of sialoliths of 1.96% (9). Kaswan et al (2014) studied the prevalence of submandibular sialoliths using periapical and occlusal radiographs and found that 5 of their 196 subjects (2.5%) suffer from submandibular sialoliths, higher than that in our study (1.8%)(10). Similarly, Vengalath et al (2014) determined a prevalence of submandibular sialoliths of 4.3% in their sample of 1615 panoramic radiographs, divided equally between males and females(11).…”
supporting
confidence: 41%
“…One of the problems associated with pulp stones is that, although a few factors are implicated in stimulating pulp calcifications, their etiology remains unknown. Pulp degeneration and its interactions with epithelium, age, systemic diseases, bacteria, genetics, fluoride, trauma, and orthodontic movements are predisposing factors [5][6][7]. Orthodontic movements can cause a complex series of tissue reactions and affect periodontal and pulpal structures [8].…”
Section: Introductionmentioning
confidence: 99%